A comparative study on the impacts of conventional care versus kangaroo mother care in the intensive care unit of Imam Hussein hospital - Soheila Khazaei (Reviews in Clinical Medicine)
Background: Approximately 20 million low-birth-weight infants are annually born worldwide. Prematurity and low birth weight are significantly linked to infant mortality rates. Neonates in neonatal intensive care units are often separated from their mothers, leading to a lack of parental involvement in care, which poses numerous risks and threats.Kangaroo mother care has been identified as an alternative method that can mitigate these risks. Methods: This semi-experimental clinical trial examined the effects of independent variables (kangaroo mother care and incubator care) on dependent variables (body temperature, weight gain, exclusive breastfeeding, and physiological measures) in 130 low birth weight infants admitted to the neonatal intensive care unit at Tehran Imam Hussein Hospital during 2019-2020.Results: This study observed an increase in maternal presence at the hospital. There were no significant differences between the two groups of mothers in terms of quantitative variables such as maternal age, number of pregnancies, and length of maternal hospital stay post-delivery. The average duration of kangaroo mother care was 12 ± 8.7 days, No differences were found between the two groups in variables such as gestational age, Apgar score, and weight and height at birth, at stability, and at discharge.Conclusion: This study demonstrated that kangaroo mother care reduces mortality, promotes exclusive breastfeeding, enhances emotional bonding between parents and neonates, reduces sepsis and patent ductus arteriosus, and shortens the duration of antibiotic use. This study supports the development of guidelines for educational programs to incorporate this alternative care method in neonatal intensive care units.